Locura y trauma en la ficción centroamericana reciente - La Haije, Marileen (Brill, 2024)
In this book, Marileen La Haije offers a thorough and innovative analysis of the intersections between madness and trauma in recent Central American literature on (post)war. A central argument of her study is that these literary texts challenge the taboo of madness in Latin American contexts of memory, by showing that talking about madness does not necessarily lead to stigmatizing victims of political violence or disqualifying their stories about traumatic experiences. La Haije highlights the importance of including madness on the research agenda in the field of memory studies in Latin America. En este libro, Marileen La Haije presenta un análisis detallado e innovador de las intersecciones entre locura y trauma en la ficción centroamericana reciente sobre la (pos)guerra. Un argumento central de su estudio es que estos textos literarios desafían el tabú de la locura en los contextos de memoria latinoamericanos, enseñándonos que hablar de locura no necesariamente implica estigmatizar a víctimas de violencia política o descalificar sus relatos sobre experiencias traumáticas. La Haije destaca la importancia de incluir la locura como tema de investigación en los estudios sobre la memoria en Latinoamérica.